School health programme practices among private secondary school administrators in an urban local government area in Lagos state, Nigeria - Adeniran, Adeyinka; Ezeiru, Sonachi (International Journal Of Community Medicine And Public Health, 2017)
Background: School Health Programmes can reduce the prevalence of health risk behaviors among young people and have a positive effect on academic performance. This study set out to assess the knowledge and the practice of school health programme among school administrators in private secondary schools in Ikeja Local Government Area (L.G.A) of Lagos State. Methods:A descriptive cross-sectional study design using a semi-structured self-administered questionnaire to obtain information on demographic data of the schools, socio-demographic data of the respondents, knowledge and practice of school health programme by the respondents and their schools respectively. This study was conducted among the 56 respondents in all the 32 registered private secondary schools in Ikeja between July and August 2010. Results: Overall, only 7.2% had good knowledge of SHP while 58.9% and 19 33.9% had fair and poor knowledge respectively. About 60% of the respondents’ schools had a school health policy, and practiced compulsory pre-admission medical examination. Although, majority of the schools (94.6%) had functional first aid box, only 28.6% had a staff in each of their building trained to use the first aid box. There’s a statistically significant association between respondents’ schools that had a School Health Policy and those that had a school clinic or health post (X2=7.2641, p=0.009). Conclusions:There was fair knowledge of SHP among the respondents while the practice of SHP in respondents’ school was also fair. There is therefore need for more awareness creation & training among school administrators for the National School Heath Policy to succeed.